Hydrogen Peroxide: Its Role in Plant Biology and Crosstalk with Signalling Networks - Černý, Martin; Habánová, Hana; Berka, Miroslav; Luklová, Markéta; Brzobohatý, Břetislav (MDPI AG (Multidisciplinary Digital Publishing Institute-MDPI), 2018)
Hydrogen peroxide (H2O2) is steadily gaining more attention in the field of molecular biology research. It is a major REDOX (reduction-oxidation reaction) metabolite and at high concentrations induces oxidative damage to biomolecules, which can culminate in cell death. However, at concentrations in the low nanomolar range, H2O2 acts as a signalling molecule and in many aspects, resembles phytohormones. Though its signalling network in plants is much less well characterized than are those of its counterparts in yeast or mammals, accumulating evidence indicates that the role of H2O2-mediated signalling in plant cells is possibly even more indispensable. In this review, we summarize hydrogen peroxide metabolism in plants, the sources and sinks of this compound and its transport via peroxiporins. We outline H2O2 perception, its direct and indirect effects and known targets in the transcriptional machinery. We focus on the role of H2O2 in plant growth and development and discuss the crosstalk between it and phytohormones. In addition to a literature review, we performed a meta-analysis of available transcriptomics data which provided further evidence for crosstalk between H2O2 and light, nutrient signalling, temperature stress, drought stress and hormonal pathways.
Keywords: H2O2; plant hormone; signalling; growth and development; stress